Market demand analysis using NLP in Bangla language - Hossain, Md Sabbir; Nayla, Nishat (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.